2016
DOI: 10.1186/s12974-016-0569-8
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines and their epistatic interactions in genetic susceptibility to schizophrenia

Abstract: BackgroundIn schizophrenia, genetic background may provide a substrate for intrinsic maldevelopment of the brain through environmental influences, by recruiting neurotrophic factors and cytokines, to trigger the changes that lead to impaired neuronal functions. Cytokines being the key regulators of immune/inflammatory reactions are also known to influence the dopaminergic, noradrenergic, and serotonergic neurotransmission. Therefore, functional polymorphisms in cytokine genes may result in imbalances in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…The first finding—that TNF‐ α −1031T/C is not significantly associated with the development of schizophrenia—is consistent with two prior studies conducted on a similar Han Chinese population demonstrating that a number of TNF‐ α single nucleotide polymorphisms, such as −238G/A, −308G/A, −857C/T, and −863C/A are not more or less prevalent in schizophrenia as compared to controls (Duan et al, ; Srinivas et al, ). However, some other studies reported that TNF‐ α −308G/A allele is a risk factor for schizophrenia when examined in North Indian, Saudi, Turkish, Pakistani, and Korean populations, indicating a possible interaction between genetic background and environment (Handoko et al, ; Kadasah, Arfin, Rizvi, Al‐Asmari, & Al‐Asmari, ; Luleyap et al, ; Pae et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The first finding—that TNF‐ α −1031T/C is not significantly associated with the development of schizophrenia—is consistent with two prior studies conducted on a similar Han Chinese population demonstrating that a number of TNF‐ α single nucleotide polymorphisms, such as −238G/A, −308G/A, −857C/T, and −863C/A are not more or less prevalent in schizophrenia as compared to controls (Duan et al, ; Srinivas et al, ). However, some other studies reported that TNF‐ α −308G/A allele is a risk factor for schizophrenia when examined in North Indian, Saudi, Turkish, Pakistani, and Korean populations, indicating a possible interaction between genetic background and environment (Handoko et al, ; Kadasah, Arfin, Rizvi, Al‐Asmari, & Al‐Asmari, ; Luleyap et al, ; Pae et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…However, some other studies reported that TNF‐ α −308G/A allele is a risk factor for schizophrenia when examined in North Indian, Saudi, Turkish, Pakistani, and Korean populations, indicating a possible interaction between genetic background and environment (Handoko et al, ; Kadasah, Arfin, Rizvi, Al‐Asmari, & Al‐Asmari, ; Luleyap et al, ; Pae et al, ). One main explanation for this discrepancy on the association between TNF‐ α −1031T/C polymorphism and the susceptibility to schizophrenia may be due to ethnic difference, since it appears that the allele frequency of the variant allele C varied markedly from different ethnicities (Duan et al, ; Handoko et al, ; Kadasah et al, ; Luleyap et al, ; Pae et al, ; Srinivas et al, ). The additional factors such as heterogeneity of the schizophrenia diagnosis, small gene effects, and population stratification may be also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed the association of a large number of single-nucleotide polymorphisms in a variety of genes with schizophrenia susceptibility 611. Genes encoding cytokines seem to be good candidate genes for schizophrenia.…”
Section: Introductionmentioning
confidence: 93%
“…The presence of G at this position defines the mutant allele known as TNF-β * 1 (1-allele), which is associated with higher TNF-α and -β production 28,29. The functional polymorphisms in cytokine genes may result in imbalances in the pro- and anti-inflammatory cytokine production 11. Keeping in view the potential role of these cytokines as the principal mediators of the immune response and the importance of the chromosomal region containing TNF-α and TNF-β genes, the present study was undertaken to examine the association of TNF-α (−308G/A) and TNF-β (+252G/A) polymorphisms with schizophrenia susceptibility in Saudi population.…”
Section: Introductionmentioning
confidence: 99%
“…For example, polymorphisms of the innate system genes, like IL1B, IL6, TNF alpha, or interferon, will lead to a bigger release of pro-inflammatory cytokines in response to environmental stressors (47). …”
Section: Biological and Clinical Features Of Patients With Autoimmunementioning
confidence: 99%